Early-life Origins of Lifecycle Well-being: Research and Policy Implications - Currie, Janet (J Policy Anal Manage, 2015)
Mounting evidence across different disciplines suggests that early-life conditions can have consequences on individual outcomes throughout the lifecycle. Relative to other developed countries, the United States fares poorly on standard indicators of early-life health, and this disadvantage may have profound consequences not only for population well-being, but also for economic growth and competitiveness in a global economy. In this paper, we first discuss the research on the strength of the link between early-life health and adult outcomes, and then provide an evidence-based review of the effectiveness of existing U.S. policies targeting the early-life environment. We conclude that there is a robust and economically meaningful relationship between early-life conditions and well-being throughout the lifecycle, as measured by adult health, educational attainment, labor market attachment, and other indicators of socio-economic status. However, there is some variation in the degree to which current policies in the U.S. are effective in improving early-life conditions. Among existing programs, some of the most effective are the Special Supplemental Program for Women, Infants, and Children (WIC), home visiting with nurse practitioners, and high-quality, center-based early childhood care and education. In contrast, the evidence on other policies such as prenatal care and family leave is more mixed and limited.